2019
DOI: 10.1038/s41561-019-0356-0
|View full text |Cite
|
Sign up to set email alerts
|

Basal melting of Ross Ice Shelf from solar heat absorption in an ice-front polynya

Abstract: Ice-ocean interactions at the base of Antarctic ice shelves are rarely observed, yet have a profound influence on ice sheet evolution and stability. Ice sheet models are highly sensitive to assumed ice shelf basal melt rates; however, there are few direct observations of basal melting or the oceanographic processes that drive this, and consequently our understanding of these interactions remains limited. Here we use new in-situ observations from the Ross Ice Shelf to examine the oceanographic processes that dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
165
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(170 citation statements)
references
References 62 publications
(78 reference statements)
4
165
1
Order By: Relevance
“…The observed heightened melting along most of the ice front (Figure ) has been previously identified from analyses of satellite laser altimetry (Horgan et al, ; Moholdt et al, ). Direct measurements of basal melt rate near Ross Island (Stewart et al, ) support the hypothesis that long‐term melt rates at Site E are dominated by rapid melting during summers when Antarctic Surface Water (AASW) has been warmed locally by insolation after the sea ice near the ice front has disappeared (e.g., Assmann et al, ; Stern et al, ; Stewart et al, ; Tinto et al, ). The subsequent advection of warmed AASW under the outer ice shelf may be driven by a combination of numerous processes including tides (Arzeno et al, ; MacAyeal, ; Makinson & Nicholls, ), eddies and other instabilities of the westward flowing ice front current (Li et al, ), and isopycnal stirring under a wedge of buoyant meltwater along the ice front (Malyarenko et al, ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The observed heightened melting along most of the ice front (Figure ) has been previously identified from analyses of satellite laser altimetry (Horgan et al, ; Moholdt et al, ). Direct measurements of basal melt rate near Ross Island (Stewart et al, ) support the hypothesis that long‐term melt rates at Site E are dominated by rapid melting during summers when Antarctic Surface Water (AASW) has been warmed locally by insolation after the sea ice near the ice front has disappeared (e.g., Assmann et al, ; Stern et al, ; Stewart et al, ; Tinto et al, ). The subsequent advection of warmed AASW under the outer ice shelf may be driven by a combination of numerous processes including tides (Arzeno et al, ; MacAyeal, ; Makinson & Nicholls, ), eddies and other instabilities of the westward flowing ice front current (Li et al, ), and isopycnal stirring under a wedge of buoyant meltwater along the ice front (Malyarenko et al, ).…”
Section: Discussionmentioning
confidence: 94%
“…However, w b varies spatially over a wide range, from close to 0 over much of the central portion of the ice shelf to over 10 m a −1 near the deep grounding line of Byrd Glacier (Kenneally & Hughes, ) and in a channel near Whillans Ice Plain (Marsh et al, ). Relatively high basal melt rates of about 1–2 m a −1 have been estimated near the ice shelf front from Lagrangian analyses of ICESat repeat‐track laser altimetry (Horgan et al, ; Moholdt et al, ) and from an autonomous phase‐sensitive radio‐echo sounder survey in a small region near Ross Island (Stewart et al, ). Satellite‐based estimates of melt rate identify extensive regions where ice appears to be accreting to the base of the ice shelf (i.e., w b < 0); however, the rates are usually smaller than the associated uncertainties (Moholdt et al, ).…”
Section: Ross Ice Shelf Structure and Mass Balancementioning
confidence: 99%
See 1 more Smart Citation
“…A reduction in sea ice formation rates could prevent this overturning and the warmer, deeper water would instead spread laterally and enhance submarine ice shelf melt, thereby thinning and weakening the shelf (Bronselaer et al, ). Other studies have shown that the direct solar heating of surface waters in polynyas (areas permanently free of sea ice) adjacent to the ice shelf front can also exacerbate sub‐shelf melting, perhaps ultimately affecting the structural stability of the whole ice shelf (Porter et al, ; C. Stewart, Christofferson, Nicholls, Williams, & Dowdeswell, ). A final possibility is that the presence of annealed pack‐ice works to mechanically inhibit iceberg calving, promoting a stronger calving front whose along‐flow strain rates are reduced compared to situations where no pack‐ice exists.…”
Section: Processes Controlling Ice Sheet Growth Stability and Decaymentioning
confidence: 99%
“…The seasonality of both HSSW production and circulation of Ice Shelf Water (ISW) from under the Ross Ice Shelf contributes to seasonal variability of Antarctic Bottom Water production near the continental shelf break (Budillon et al, 2011). Local warming of the upper ocean near the Ross Ice Shelf front, which contributes to the observed rapid melting in the ice shelf's frontal zone (Arzeno et al, 2014;Horgan et al, 2011;Malyarenko et al, 2019;Moholdt et al, 2014;Stewart et al, 2019;Tinto et al, 2019), only occurs during austral summer when there is minimal sea ice. The southward flux and hydrographic properties of the subsurface layer of modified Circumpolar Deep Water (mCDW) near Hayes Bank also vary seasonally (Pillsbury & Jacobs, 1985).…”
Section: Introductionmentioning
confidence: 99%